The Advanced Eccentricity and Broken Cage Diagnostic Method for Medium Voltage Induction Motors - Janda, Žarko S.; Janković, Marko V.; Milošević, Mladen S.; Jovanović, Blagota T. (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
In the paper the comparative diagnostics of medium voltage induction motors has been presented. The methods employed are the motor current signature analysis (MCSA) and the axial leakage flux spectral analysis. All presented test procedures have been conducted on partially loaded motors, one without fault and the other with fault. Rated parameters of case study motors are 6 kV and 3.15 MW, and both motors are installed in one combined steam power plant. The reliable broken rotor bars detection and existence of static eccentricity have been demonstrated. The new method for combined fault detection has also been announced. The combined fault under scope is the simultaneous existence of broken rotor bars and static eccentricity. The proposed combined fault detection method is based upon axial leakage flux spectral analysis, especially in the vicinity of the double fundamental frequency. The existence of three broken rotor bars has been confirmed after physical rotor cage examination.